Cultural entrepreneurial opportunities: a business network perspective - Cantú, Chiara (Piccola Impresa / Small Business, 2025)
Purpose. This paper aims to investigate how the entrepreneurial network can support the exploitation of cultural entrepreneurial opportunities. In particular, this paper analyses the foundation of a startup belonging to the CCIs and its evolution in the early-stage. Design/methodology. This study adopts a qualitative research approach and a case study design. The case study concerns a film-startup in the audiovisual industry that has reached its early stage. The startup founded its development on business and non business relationships with key organizations in the Lake Como area. Qualitative data were collected through semi-structured interviews. Primary and secondary data were integrated. Findings. Findings reveal that exploiting cultural entrepreneurial opportunities requires a shift from an individual perspective to an interorganizational perspective, considering the development of business and non business relationships with heterogeneous stakeholders. In particular, local relationships based on regional values encourage the transition from local cultural opportunities to cultural entrepreneurial opportunities, creating a virtuous circle: CEOs generate a positive impact on startups and business activities in the territory. The combination of geographical and cultural proximity with relational proximity has fostered the relationships that characterize the network context, improving the sense of collectivism even within organizations. Practical and social implications. Exploiting cultural entrepreneurial opportunities requires combining heterogeneous competences through interorganizational relationships. The integration of cultural and business goals that characterize cultural organizations is based on the development of business and non business relationships with different organizations. Mapping key actors and innovative networking practices can improve the achievement of cultural and business goals. Originality of the study. This study contributes to the analysis of cultural entrepreneurial opportunities generated at meso level, considering the collaboration between a new CCIs venture and various organizations belonging to the territory. Furthermore, the paper responds to the call for an in-depth analysis of how actors work collectively to support the development of new entrepreneurial ventures. Differently from previous studies focused on inidiviual-micro level, this paper considers the inter-organizational perspective in cultural entrepreneurship.